PLACES OF CRI-ACTIVE AGING - Rocha, Eduardo; Resende, Lorena Maia; Portella, Adriana Araújo; Woolrych, Ryan (Mercator, 2022)
Brazil, like other countries in the world, has been showing an increasingly long-lasting population growth. Over the last decade, much research has focused on understanding the complexity and impacts of aging. However, it is still not clear whether there is any relationship between the specific ways of life of the elderly and the sense of place they experience. We ask: what places and types of activities can contribute to a better quality of life for the elderly in their home, neighborhood, neighborhood and city? In order to analyze how the elderly live with the places they inhabit in contemporary urbanity, in order to provide new strategies for inclusive urban planning, the research used the method of photographic diaries to understand these dynamics. The study was applied in the Brazilian cities of Pelotas/RS, Belo Horizonte/MG and Brasília/DF, each one with three sections of neighborhoods chosen by different income groups (high, medium and low). Even with their great urban, economic and cultural differences, these cities have in common the transformations in the age pyramid, making the study more heterogeneous and diverse. As a result, it was possible to approach the concept of “becoming-child”, bringing together contemporary French philosophy with the sense of "good place" found in the elderly in the research. These coexistences led us to propose the exercise of composition of a “becoming-child-elderly”, towards a will to power and affirmation of architectural and urban life for a “creative-active” elderly person. Keywords : Aging, Photographicdiaries, Becoming-Child-Elderly, Territories, Elderlyfriendlycity,Senseofplace.